Safety, feasibility and learning curve of robotic single‐site surgery in gynecology. Issue 3 (11th June 2015) - El Hachem, Lena; Momeni, Mazdak; Friedman, Kathryn; Moshier, Erin L.; Chuang, Linus T.; Gretz, Herbert F.
Abstract: Background: Robotic single‐site (RSS) surgery has emerged as a novel minimally invasive approach in gynecology. Methods: Retrospective cohort study of consecutive RSS gynecologic procedures undertaken between October 2013 and March 2014. Results: The 25 RSS completed cases consisted of 11 adnexal and 14 hysterectomy cases of which three included pelvic lymphadenectomies. Mean age, body mass index and estimated blood loss were 51 years, 25 kg/m 2, 30 mL in the adnexal group, respectively, and 58 years, 27 kg/m 2, 96 mL in the hysterectomy group, respectively. Mean console time was 20 and 45 min and mean total operative time was 56 and 93 min in adnexal and hysterectomy cases, respectively. The CUSUM method identified two learning phases with significant reduction in console time after the 7th adnexal case and the 5th hysterectomy. Conclusion: When performed by advanced minimally invasive surgeons and in appropriately selected patients, RSS surgery is feasible and safe. Copyright © 2015 John Wiley & Sons, Ltd.